CHARACTERISTICS OF SCIENTIFIC NURSING PRODUCTION ON TRANSPLANTATION OF HEMATOPOIETIC STEM CELLS - Kaoana Lima; Elizabeth Bernardino; Lillian Wolff; Aida Peres (Universidade Federal do Paraná, 2012)
An integrative literature review with the objective of identifying and characterizing the Nursing scientific production on the transplantation of hematopoietic stem cells, indexed in the Nursing Database, the Latin-American and Caribbean System on Health Sciences Literature and the Scientific Electronic Library Online, using the descriptors nursing and transplantation of bone marrow. In the 29 articles which resulted from the analysis, there was a predominance of articles from the Southwest and South regions of Brazil, from Post-graduate programs, and published by nurses directly involved in care, lecturers, and post-graduate students. The issues addressed refer to the care actions and the nursing care given to the patients and their family members during the transplantation process, the therapeutic process, the organization of the work and the production of Nursing knowledge in transplantation. It was ascertained that production in this area is incipient, as despite the fact that it is growing, there are still subjects which have not been explored.